Respuesta :

Answer: (2, 9)

Step-by-step explanation:

[tex]\lbrace^{y=5x-1 }_{2y=3x+12}}[/tex]

Since "y" = "5x - 1", we can replace "y" in the second equation with "5x - 1"

    2y = 3x + 12

⇒ 2(5x - 1) = 3x + 12    substituted "y" with "5x - 1"

⇒ 10x - 2 = 3x + 12     distributed 5x - 1 by 2 on left side

⇒  7x - 2 = 12              subtracted 3x from both sides

⇒  7x = 14                    added 2 to both sides

⇒ x = 2                         divided both sides by 2


Next, let's solve for y by substituting "x" with "2":

y = 5x  - 1

  = 5(2) - 1

  = 10 - 1

  = 9